Role of pro-brain-derived neurotrophic factor (proBDNF) to mature BDNF conversion in activity-dependent competition at developing neuromuscular synapses - Je, H. Shawn (National Academy of Sciences, 2012)
Formation of specific neuronal connections often involves competition between adjacent axons, leading to stabilization of the active terminal, while retraction of the less active ones. The underlying molecular mechanisms remain unknown. We show that activity-dependent conversion of pro–brain-derived neurotrophic factor (proBDNF) to mature (m)BDNF mediates synaptic competition. Stimulation of motoneurons triggers proteolytic conversion of proBDNF to mBDNF at nerve terminals. In Xenopus nerve–muscle cocultures, in which two motoneurons innervate one myocyte, proBDNF-p75(NTR) signaling promotes retraction of the less active terminal, whereas mBDNF–tyrosine-related kinase B (TrkB) p75NTR (p75 neurotrophin receptor) facilitates stabilization of the active one. Thus, proBDNF and mBDNF may serve as potential “punishment” and “reward” signals for inactive and active terminals, respectively, and activity-dependent conversion of proBDNF to mBDNF may regulate synapse elimination.